Barriers and potential solutions to international collaboration in neuro‐oncology clinical trials: Challenges from the Australian perspective. Issue 3 (24th June 2021) - Kong, Benjamin Y.; Carter, Candace; Nowak, Anna K.; Hovey, Elizabeth; Lwin, Zarnie; Haghighi, Neda; Gan, Hui K.; Sim, Hao‐Wen; Ziegler, David S.; Barton, Kirston; Parkinson, Jonathon; Leonard, Robyn; et al.
Abstract: Aim: The neuro‐oncology community in Australia is well positioned to collaborate internationally, with a motivated trials group, strong regulatory bodies and an attractive fiscal environment. We sought to identify gaps in the Australian neuro‐oncology clinical trials landscape and describe strategies to increase international trial access in Australia. Methods: We searched clinical trial registries to identify active adult primary brain cancer trials. We compared the participation rate and phase of these trials between tumour types and countries. A survey was distributed to the Cooperative Trials Group for Neuro‐Oncology membership to identify barriers and solutions to effective international collaboration. Results: Globally, 307 trials for adult primary brain cancers were identified. These included 50% pharmaceutical agents, 18% cellular therapies and 9% radiation therapy. Twelve adult primary brain cancer trials were actively recruiting in Australia at the time the survey was sent out. There were more early phase brain cancer trials (34%) compared with colorectal and breast cancer (21% and 24%, respectively). In Australia, 92% of brain cancer trials were involving pharmaceutical agents. The most commonly cited barrier was lack of funding for international trials (86%) and insufficient research time (75%). High ranking solutions included increasing the availability of funding for international trials and creating opportunities to develop personal relationships with collaborators. Accreditation of clinical research key performance indicators into practice (88%) and hospital accreditation (73%) also ranked highly. Conclusions: Participation in international research in Australia could be improved by embedding clinical research targets into institutional funding, provision of funding for early phase studies and streamlining mutual ethics schemes. Abstract : International collaboration in neuro‐oncology in Australia is hampered by a small, highly heterogeneous patient population. Participation in international clinical research could be improved by funding‐linked clinical research targets, streamlining of mutual ethics schemes and infrastructure funding for early phase studies.